Study of algorithms for decomposition of a numerical semigroup - Branco, M.B. (2012)
We study two algorithms to decompose a numerical semigroup S as intersection of irreducible numerical semigroups. We also present a compared study of two algorithms to compute the intersection of two numerical semigroups with embedding dimension two and the same multiplicity.